Некоторые подробности применения метода конечных элементов в фотоупругости - Тесленко, А. А. (НТУ "ХПИ", 2006)
Bases of a new modification of photoelasticity method and possibility of its model research are examined in work. Essence of a new modification consists of combination of possibilities of traditional photoelasticity method and finite-element method. Estimation of influencing of exactness of setting of the explored body on exactness in determination of tensions in the conditions of particular matter and chart of measuring is produce
Keywords: поляризационно-оптическая томография; метод конечных элементов; деформация; метод разности касательных напряжений